2016
DOI: 10.1136/postgradmedj-2016-134496
|View full text |Cite
|
Sign up to set email alerts
|

Constructing diagnostic likelihood: clinical decisions using subjective versus statistical probability

Abstract: Physicians are strongly influenced by a representativeness bias, leading to base-rate neglect, even though they understand the application of statistical probability. One of the causes for this representativeness bias may be the way clinical medicine is taught where stereotypic presentations are emphasised in diagnostic decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The findings regarding the base rate fallacy are diverse. While an older study by Weber and colleagues only showed little prevalence of base rate neglect (Weber et al, 1993), a recent study by Kinnear & Jackson (2016) identified the major evidence of representativeness heuristic, resulting in base rate neglect. The latter study also identified that base rate neglect occurred despite a good understanding of statistical probability concepts.…”
Section: Empirical Data On the Prevalence Of Decision-making Biases In Medicinementioning
confidence: 94%
See 1 more Smart Citation
“…The findings regarding the base rate fallacy are diverse. While an older study by Weber and colleagues only showed little prevalence of base rate neglect (Weber et al, 1993), a recent study by Kinnear & Jackson (2016) identified the major evidence of representativeness heuristic, resulting in base rate neglect. The latter study also identified that base rate neglect occurred despite a good understanding of statistical probability concepts.…”
Section: Empirical Data On the Prevalence Of Decision-making Biases In Medicinementioning
confidence: 94%
“…The latter study also identified that base rate neglect occurred despite a good understanding of statistical probability concepts. One possible explanation for this dissonance could be that the teaching of diagnostic decision-making foregrounds stereotypic presentations of diseases (Kinnear & Jackson, 2016).…”
Section: Empirical Data On the Prevalence Of Decision-making Biases In Medicinementioning
confidence: 99%